Genetic Diversity and Population Structure of Zingiber officinale Roscoe in Northern Mato Grosso State, Brazil - Cardoso, Elisa dos Santos; Rossi, Ana Aparecida Bandini; Pedri, Eliane Cristina Moreno de; Zortéa, Kelli Evelin Müller; Cuchi, Giovana; Ferreira, Edimilson Leonardo; Silva, Vantuir Pereira da (American Scientific Research Journal for Engineering, Technology, and Sciences, 2022)
The ginger (Zingiber officinale Roscoe) was introduced in Brazil in the 16th century and is currently cultivated for commercial purposes and for own consumption, in urban and rural backyards. Although the species reproduces vegetatively, the exchange of rhizomes among gardeners contributes to the maintenance of the genetic variability of the species, since they carry out the selection of genotypes adapted to the soil and climate conditions of the cultivation areas. Studies on the variability of ginger cultivated in Brazil are scarce, therefore this study aimed to evaluate the genetic diversity and population structure, using ISSR molecular markers, of 245 ginger specimens cultivated in rural and urban backyards of twenty municipalities (populations) in the state of Mato Grosso, Brazil. The ISSR primer set used was classified as moderately informative and it amplified a total of 105 fragments, of which 97.60% showed polymorphism, indicating the existence of genetic variability. The genetic diversity assessment separated the 245 specimens into 30 hierarchical groups. Group 1 was the most representative (72%), containing specimens from all populations sampled. The population-level assessment allocated 18 populations in a single group, while the populations of Apiacás and Peixoto de Azevedo formed exclusive groups. The Molecular Variance Analysis revealed that the genetic variation found within populations (76.58%) is greater than that found among populations (23.42%), which indicates a process of fixing of alleles and genetic structuring. The Bayesian analysis identified only two distinct genetic groups and some populations sampled showed a predominance of one of the groups, which evidences the process of genetic structuring. According to the genetic distance of Nei (h) and the Shannon Index (I), Apiacás was the population that presented the greatest genetic diversity, while Matupá was characterized as the population with less diversity. The genetic diversity found indicates that the cultivation, handling and selection performed by gardeners, as well as the exchange of rhizomes for propagation, are important factors for the conservation of the genetic diversity of the species. We also concluded that backyards are a source of genetic resources for programs that aim to identify traits of interest and promote the cultivation of the species in Brazil.